PERIODE FORMATIF/KLASIK DAN AFIRMATIF/PERTENGAHAN MAZHAB TAFSIR: (Kajian Sumber, Metode, Corak, Karakteristik, dan Tokoh Mufassir) - Muhammad Raihannur; Siti Sa’adatul Rizkiyah (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2026)
The development of Quranic exegesis (tafsir) has undergone significant historical phases that form the foundation of Islamic intellectual tradition. This article examines two pivotal periods in the history of tafsir: the formative/classical period and the affirmative/medieval period. Using a historical-descriptive approach through library research, this study analyzes the sources and methods, characteristics, and key exegetes (mufassirin) of each period. The formative/classical period, spanning from the era of the Prophet Muhammad to the tabi'in generation, was characterized by reliance on riwayah-based interpretation (bil-ma'tsur), oral transmission, and the authority of prophetic traditions and companions' opinions. The affirmative/medieval period witnessed a significant expansion in methodology and thematic corak, integrating disciplines such as jurisprudence (fiqh), theology (kalam), philosophy, and Sufism into Quranic interpretation. Prominent figures such as al-Tabari, al-Zamakhshari, al-Razi, Ibn Kathir, and al-Qurtubi produced monumental works during the latter period. The study concludes that both periods represent a continuum of scholarly endeavor, with the formative period establishing normative foundations and the medieval period consolidating and diversifying the exegetical tradition